Answer:
Option 1
Explanation:
To find out the equivalent expression, expand all of the expressions by multiplying the number outside the bracket and its sign with each term inside the bracket.
Given expression:
-(1/2 y + 1/4)
= -1/2 y -1/4
Option 1:
-1/4(1 +2y)
= -1/4 -1/4(2y)
= -1/4 -1/2 y
= -1/2 y -1/4
(equivalent)
Let's check the other options.
Option 2:
1/4(2y -1)
= 1/4(2y) -1/4
= 1/2 y -1/4
(not equivalent)
Option 3:
-2(1/4 y - 1/8)
= -2(1/4y) -2(-1/8)
= -1/2y +1/4
(not equivalent)
Option 4:
2(1/8 -1/4 y)
=2(1/8) -2(1/4 y)
= 1/4 -1/2y
= -1/2y +1/4
(not equivalent)
Thus, the correct answer is option 1.